Representation of Family Values in the Film 1 Imam 2 Makmum (2025): John Fiske’s Semiotic Analysis of Gender Representation in Popular Narrative - Melinda Ratmayanti; Yudha Wirawanda (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − This study examines the representation of family values in the film 1 Imam 2 Makmum (2025) using John Fiske’s semiotic approach. Through three levels of analysis—reality, representation, and ideology—it finds that the film portrays family dynamics constructed upon particular value systems, where men are depicted as rational decision-makers and women as emotional and domestic stabilizers. Method − This research employs a descriptive qualitative approach within a critical paradigm, meaning the researcher serves as the primary instrument. Findings − This method allows for an in-depth exploration of film elements related to John Fiske’s semiotic analysis. The main findings indicate that the division of roles and communication patterns are symbolically represented through visual aesthetics, dialogue, and framing, which together shape gender relations within the household. The film also illustrates processes of negotiation and emotional recognition, suggesting that family identity is constructed through a combination of authority, care, and adaptation. These subtle symbolic representations demonstrate how contemporary popular media both shapes and reflects social discourse on family and gender